The Logical Framework and Temporal Value of Common Prosperity - Xiao, Lihua (Transactions on Economics, Business and Management Research, 2023)
Human common prosperity is a global and significant social issue. This paper examines how China is advancing the construction of common prosperity from three perspectives: culture, history, and society. It delineates the three major logical relationships of historical logic, theoretical logic, and practical logic. In the implementation process, common prosperity is placed at the forefront, capturing the crucial direction, relationships, dimensions, and observing progress through five major development indicators. This has marked the beginning of a new era of prosperity for humanity, enriched the meaning of modernization for humankind, and hoisted the flag of scientific socialism high on the world stage.